Endogenous Derivatives of Linoleic Acid and their Stable Analogs Are Potential Pain Mediators - Joshua J. Wheeler; Anthony F. Domenichiello; Jennifer R. Jensen; Gregory S. Keyes; Kristen M. Maiden; John M. Davis; Christopher E. Ramsden; Santosh K. Mishra (Elsevier, 2023)
Psoriasis is characterized by intense pruritus, with a subset of individuals with psoriasis experiencing thermal hypersensitivity. However, the pathophysiology of thermal hypersensitivity in psoriasis and other skin conditions remains enigmatic. Linoleic acid is an omega-6 fatty acid that is concentrated in the skin, and oxidation of linoleic acid into metabolites with multiple hydroxyl and epoxide functional groups has been shown to play a role in skin barrier function. Previously, we identified several linoleic acid‒derived mediators that were more concentrated in psoriatic lesions, but the role of these lipids in psoriasis remains unknown. In this study, we report that two such compounds-9,10-epoxy-13-hydroxy-octadecenoate and 9,10,13-trihydroxy-octadecenoate-are present as free fatty acids and induce nociceptive behavior in mice but not in rats. By chemically stabilizing 9,10-epoxy-13-hydroxy-octadecenoate and 9,10,13-trihydroxy-octadecenoate through the addition of methyl groups, we observed pain and hypersensitization in mice. The nociceptive responses suggest an involvement of the TRPA1 channel, whereas hypersensitive responses induced by these mediators may require both TRPA1 and TRPV1 channels. Furthermore, we showed that 9,10,13-trihydroxy-octadecenoate‒induced calcium transients in sensory neurons are mediated through the Gβγ subunit of an unidentified G-protein coupled receptor (GPCR). Overall, mechanistic insights from this study will guide the development of potential therapeutic targets for the treatment of pain and hypersensitivity.